Processing of Starch in Deep Eutectic Solvent. (10th July 2022) - Deng, Xiaonan; Zhang, Mengnan; Liu, Kun; Pu, Mingdong; Han, Xiaozhao
Abstract: The deep eutectic solvent of [choline chloride (ChCl)] [ethylene glycol (EG)] is demonstrated to be an effective non‐destructive solvent for starch processing. The pre‐gelatinized starch samples are prepared by its gelatinization, treatment, and re‐crystallization in this deep eutectic solvent and characterized by differential scanning calorimetry (DSC), gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance spectroscopy (H‐NMR), X‐ray diffraction analyses (XRD), and scanning electron microscopy (SEM) tests. The gelatinization temperature of starch in the deep eutectic solvent of [choline chloride] [ethylene glycol] is measured using a DSC method. Compared to the native starch sample, slight increases in molecular weights and decreases in molecular weight distribution of the recovered starch samples are observed. The similar FTIR and H‐NMR spectra of the native starch and recovered starch samples suggest no reaction and variation in chemical structure during the processing. The XRD and DSC tests show that the strong micro‐granular crystalline structure of the native corn starch is destroyed during the gelatinization and treatment in the DES while new weak crystalline structure is formed during the re‐crystallization. Abstract : Corn starch is processed in DES of [ChCl] [EG] and the nondestructive solvent is confirmed by a GPC test. The XRD and DSC tests show the disappearance of strong crystalline granular structure during the gelatinization and the formation of weak new crystalline structure during the re‐crystallization.